2016
DOI: 10.1007/s12640-016-9615-7
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Affects the Neurogenesis of the Hippocampal Dentate Gyrus in 7-Day-Old Rats

Abstract: Ketamine has been reported to cause neonatal neurotoxicity via a neuronal apoptosis mechanism; however, no in vivo research has reported whether ketamine could affect postnatal neurogenesis in the hippocampal dentate gyrus (DG). A growing number of experiments suggest that postnatal hippocampal neurogenesis is the foundation of maintaining normal hippocampus function into adulthood. Therefore, this study investigated the effect of ketamine on hippocampal neurogenesis. Male Sprague-Dawley rats were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 47 publications
7
50
0
Order By: Relevance
“…In line with our results, ketamine as well as other classical antidepressants such as imipramine and fluoxetine or agomelatine increase or normalize dentate gyrus proliferation and neurogenesis, which could be essential for the therapeutic effects. Interestingly, both NMDAR activation as well as blockade has been associated with an increase proliferation and differentiation in the dentate gyrus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our results, ketamine as well as other classical antidepressants such as imipramine and fluoxetine or agomelatine increase or normalize dentate gyrus proliferation and neurogenesis, which could be essential for the therapeutic effects. Interestingly, both NMDAR activation as well as blockade has been associated with an increase proliferation and differentiation in the dentate gyrus.…”
Section: Discussionsupporting
confidence: 90%
“…Changes in this process have been implicated in the development of depression and are thus a possible target for the actions of ketamine. Although the nature of the proliferating cells is unknown, there are previously reported effects of ketamine and pre‐natal stress on dentate gyrus neurogenesis. Pre‐natal stress inhibits dentate gyrus but not olfactory bulb neurogenesis and chronic mild stress impacts survival but not proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…injection of ketamine or multiple (six times) consecutive i.p. injections of ketamine at 1-h intervals, based on the methods described in previous studies (Huang et al, 2015, 2016), with modifications. For both single and multiple administrations, mice were randomly assigned to five groups, with 12 mice per group: saline-treated group, 10 mg/kg ketamine group, 20 mg/kg ketamine group, 40 mg/kg ketamine group, and 80 mg/kg ketamine group.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 70% of patients with lung cancer present with locally advanced or metastatic disease at the time of diagnosis, and there terminal stage of cancer [5,6]. In a series of animal experiments, ketamine has been shown to promote neuronal apoptosis and induce cell death in neurons and neural stem progenitor cells [7][8][9]. Moreover, our previous study also revealed that repeated administration of ketamine can induce hippocampal neurodegeneration [10].…”
Section: Introductionmentioning
confidence: 98%